Think Pair Share dengan Komik terhadap Kemampuan Pemecahan Masalah Matematis - Lukman Kalbuadi; Annis Deshinta Ayuningtyas; Sri Adi Widodo (Journal of Instructional Mathematics, 2020)
The purpose of this study was to determine whether the Think Pair Share learning model assisted by comics was more effective than without using comics for the ability to solve mathematical problems. This research is included in quasi-experimental research because it has a control group, but it cannot function fully in controlling external variables that affect the implementation of the experiment. The population of this study was all students of class VII of SMP Negeri 5 Yogyakarta in the second semester of 2018/2019 academic year. The sampling technique used is the Random Cluster technique. The results showed that the TPS-assisted comic-learning model was no more effective than the TPS-without comic-learning model in terms of mathematical problem-solving abilities